2020
DOI: 10.15389/agrobiology.2020.1.184eng
|View full text |Cite
|
Sign up to set email alerts
|

ROLE OF METEOROLOGICAL FACTOR IN LONG-TERM POPULATION DYNAMICS OF THE EUROPEAN CORN BORER, Ostrinia nubilalis Hbn., IN KRASNODAR AREA: THE ANALYSIS OF LIFE TABLES

Abstract: Кукурузный мотылек Ostrinia nubilalis Hbn. -один из наиболее опасных вредителей кукурузы. Хотя важная роль метеорологических условий, в первую очередь температуры и влажности воздуха, многократно продемонстрирована в отношении распространения, численности и сроков развития кукурузного мотылька, точность существующих моделей прогноза размножения вредителя остается невысокой. Цель нашей работы состояла в сопоставлении метеорологических данных с демографическими показателями, характеризующими многолетние колебани… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Still, the eggs laid by the females do not have favorable conditions of temperature and humidity for the larvae to hatch. In their study, Frolov and Grushevaya [ 43 , 44 ] found that some of the larvae, up to 30%, pupated, and a new generation appeared. The same conclusion was reached by Barbulescu [ 45 , 46 , 47 ], who observed that in southern Romania’s conditions, 20% of the larvae transform into pupae, and a second generation of moths appears.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the eggs laid by the females do not have favorable conditions of temperature and humidity for the larvae to hatch. In their study, Frolov and Grushevaya [ 43 , 44 ] found that some of the larvae, up to 30%, pupated, and a new generation appeared. The same conclusion was reached by Barbulescu [ 45 , 46 , 47 ], who observed that in southern Romania’s conditions, 20% of the larvae transform into pupae, and a second generation of moths appears.…”
Section: Discussionmentioning
confidence: 99%
“…In the central chernozem region of Russia the yield losses reached 15% in maize (SHPANEV et al 2019). The intensity of attack of Ostrinia nubilalis varied from year to year depends of climatic condition (FROLOV and GRUSHEVAYA, 2020). In their study reported that European corn borer (ECB) population dynamics significantly related to environmental condition and that survival egg and larva depending from air temperature and air humidity during the last decade of May in the Krasnodar area, what confirmed earlier study which reported significant effect of weather conditions on ECB infestation in sweet maize (VELASCO et al, 2007;KESZTHELYI, 2010;MAIORANO, 2012;WALIGÓRA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%